parental style and its relationship to perfectionism among outstanding students (Field study in the city of Latakia) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
The research aims to identify the relationship between parental styles and perfectionism among a sample  of  outstanding students in the city of Latakia, identify common parental styles from the children’s point of view, and reveal their level of perfectionism. The researcher used the parental style scale prepared by her, and the neurotic perfectionism scale prepared by Al-Quraity et al, and followed the descriptive approach to achieve the objectives of the study. The sample consisted of 166 male and femal student from schools for outstanding students in the seven and eighth grades.The results of the study revealed that the common positive parental style among the outstanding students from their point of view are democracy and encouragement, while the negative style were at a moderate level, which are overprotection, pampering, feeling of guilty, and domineering, the result also revealed a moderate level of neurotic perfectionism among the outstanding students, in addition to there is a relationship between their parental styles and their perfectionism.
Keywords: Parental style, Neurotic perfectionism, outstanding students.